The development of entrepreneurial competencies: a transdisciplinary approach - Guerra Velásquez, Mauricio Esteban (2022)
Entrepreneurial competencies are a major topic of interest within the field of entrepreneurship, providing a better understanding of the generation and development of new ventures across different settings (Ardichvili, Cardozo, & Ray, 2003; Chandler & Jansen, 1992; Hayton & Kelley, 2006). In the area of academic entrepreneurship, the work of Rasmussen and colleagues (Rasmussen, Mosey & Wright., 2011, 2014, 2015; Rasmussen & Wright, 2015) have recognised that entrepreneurial competencies play a critical role in the development of university spinoffs. However, what is not yet clear is the impact of the broader context of academic entrepreneurship on entrepreneurial competency development.